2003
DOI: 10.1016/s0168-6445(02)00128-6
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based identification of Bacillus thuringiensis pesticidal crystal genes

Abstract: The polymerase chain reaction (PCR) is a molecular tool widely used to characterize the insecticidal bacterium Bacillus thuringiensis. This technique can be used to amplify specific DNA fragments and thus to determine the presence or absence of a target gene. The identification of B. thuringiensis toxin genes by PCR can partially predict the insecticidal activity of a given strain. PCR has proven to be a rapid and reliable method and it has largely substituted bioassays in preliminary classification of B. thur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 41 publications
3
75
0
2
Order By: Relevance
“…The most common cry genes found in nature are those within the cry1 subfamily (Porcar and Juárez-Pérez 2003). The most abundant gene found in our collection was cry2, and the second most abundant was the cry1 gene family.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The most common cry genes found in nature are those within the cry1 subfamily (Porcar and Juárez-Pérez 2003). The most abundant gene found in our collection was cry2, and the second most abundant was the cry1 gene family.…”
Section: Discussionmentioning
confidence: 84%
“…The identification of Bt cry genes by PCR has proven to be a very useful method for strain characterization and selection (Porcar and Juárez-Pérez, 2003). In addition Carozzi et al (1991) found correspondence of toxicity with the amplification of particular cry gene profiles, introducing PCR as a tool to predict B. thuringiensis insecticidal activity.…”
mentioning
confidence: 99%
“…Strains in the collections are characterized by a number of different methods to identify and to test and confirm their toxicity against different insect orders (Arango et al, 2002;Wang et al, 2003;Tamez-Guerra et al, 2004;Martinez et al, 2005). Identification of cry gene content by PCR is the most effective technique in screening large native collections to predict insecticidal activities of individual strains (Ben-Dov et al, 1997;Porcar and Juarez-Perez, 2002). In addition, serolog-ical analysis, biological activity tests, plasmid contents, chromosomal DNA, and protein profiling are used as complementary methods in the search for novel strains.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of cry genes by means of PCR has been used to predict insecticidal activity of the strains [17,18] and to determine the distribution of cry genes within a collection of B. thuringiensis strains [20,33]. In this context, our crystalliferous strains were characterized in terms of presence of cry1 and cry2 genes by amplification with general primers.…”
Section: Molecular Characterization Of B Thuringiensis Strains and Cmentioning
confidence: 99%
“…The literature data report the possibility of using the whole-cell protein profile as a discriminating method with potency similar to RAPD with combined DNA patterns [1]. However, there is not always a good correlation between these factors and insecticidal activity of Bt strains [20,21]. In addition, there is a need to develop knowledge about the biological properties and diversity of Bt isolates since these data allow a better understanding of the biological factors that determine insecticidal properties.…”
Section: Introductionmentioning
confidence: 99%